2016
DOI: 10.1038/ncomms13049
|View full text |Cite
|
Sign up to set email alerts
|

Classical non-homologous end-joining pathway utilizes nascent RNA for error-free double-strand break repair of transcribed genes

Abstract: DNA double-strand breaks (DSBs) leading to loss of nucleotides in the transcribed region can be lethal. Classical non-homologous end-joining (C-NHEJ) is the dominant pathway for DSB repair (DSBR) in adult mammalian cells. Here we report that during such DSBR, mammalian C-NHEJ proteins form a multiprotein complex with RNA polymerase II and preferentially associate with the transcribed genes after DSB induction. Depletion of C-NHEJ factors significantly abrogates DSBR in transcribed but not in non-transcribed ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
194
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(224 citation statements)
references
References 49 publications
10
194
0
Order By: Relevance
“…12, 44 Again in yeast, an even more recent paper also demonstrates the formation of RNA:DNA hybrids at sites of DNA damage, showing a strong link between transcription and DNA repair. 45 Alternatively, they may also be involved in the process of modulating chromatin states, in a manner similar to piwi -interacting RNA in germ cells.…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 98%
“…12, 44 Again in yeast, an even more recent paper also demonstrates the formation of RNA:DNA hybrids at sites of DNA damage, showing a strong link between transcription and DNA repair. 45 Alternatively, they may also be involved in the process of modulating chromatin states, in a manner similar to piwi -interacting RNA in germ cells.…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 98%
“…Interestingly, Chakraborty et al recently showed that non-homologous end joining proteins preferentially associate with transcribed sequences following DSB induction and facilitate an error-free mechanism of DSB repair in transcribed DNA in mammalian cells (Chakraborty et al, 2016), supporting an RNA-guided DSB repair mechanism occurring prior to extensive end resection at the DSB ends. Here, we propose that Rad52 inverse RNA strand exchange can contribute to RNA-directed DSB repair in conditions of limited end resection by generating a heteroduplex between RNA and homologous DNA at the site of DSBs, in which RNA serves as a bridging template guiding DSB repair with or without a short gap filling synthesis (Figure 6).…”
Section: Discussionmentioning
confidence: 99%
“…The biological role of Rloops is currently under intense investigation. It was found that R-loops are essential for repair of DNA double-strand breaks in actively transcribed genome regions through TC-HR (Marnef et al, 2017;Wei et al, 2016;Yasuhara et al, 2018) or Non-Homologous End-Joining (Chakraborty et al, 2016). It was proposed by Kogoma that R-loops may serve as a primer to restart DNA replication stalled at DNA lesions (Kogoma, 1997) ( Figure 7).…”
Section: Rpa-rna Interactions In Vivomentioning
confidence: 99%